(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the improvement in the mathematical comprehension ability of class VII B students of SMPK St. Paulus Karuni after the implementation of ethnomathematics-based mathematics learning based on traditional houses. The study used a quantitative approach with a pre-experimental design of the One Group Pretest–Posttest Design. The research subjects were 21 class VII B students of SMPK St. Paulus Karuni. Data were collected through mathematical comprehension ability tests given before (pretest) and after learning (posttest), as well as observation sheets for the implementation of learning. Data analysis was carried out using descriptive statistics to describe the achievement of student learning outcomes, Normalized Gain (N-Gain) calculations to determine the level of improvement in mathematical comprehension abilities, and percentage analysis to assess the implementation of learning. The results showed that the average pretest score of students was 44.48, increasing to 92.57 in the posttest. The results of the N-Gain analysis obtained an average of 0.89 which is included in the high category. In addition, the implementation of learning reached 100% with a very good category. These findings indicate that ethnomathematics-based mathematics learning based on traditional houses is effective in improving students’ mathematical comprehension abilities. Integrating local culture into learning helps students understand mathematical concepts in a more concrete, contextual, and meaningful way.